Corneal Endothelial Cell Changes with the Age in Normal Iraqi Population Using Em-3000 Tomey Speculer Microscope - Mohanad M. Hasan, Dr. (International Journal of Engineering and Technology, 2018)
"Background: The cornea consists of the following layers, each of which is critical to normal function: 1. Epithelium. 2. Bowman layer. 3. Stroma. 4. Descemnts membrane. 5. Endothelium. The corneal endothelium is composed of a single layer, mostly of hexagonal cells. Approximately 500,000 cells are present, with a density of about 3000 cells/mm2. The size, shape, and morphology of the endothelial cells can be observed by specular microscopy at the slit lamp". "Patients and methods: 400 eyes of 200 patients who attended the ophthalmology department in Al-Zahraa teaching hospital were included in the study. Patients were grouped into five groups according to age: [G1] less than 20 years. [G2] 20-30 years. [G3] 31-40 years. [G4] 41-50 years. [G5] more than 50 years so, we have five age groups. Patients with history of intraocular surgery or ocular trauma, increased intraocular pressure, uveitis, corneal opacity, evidence of endothelial dystrophy on slit-lamp bio microscopy, diabetes mellitus and contact lens wearer were excluded from the study. After routine ophthalmic examination, all patients underwent specular microscopy using a noncontact specular microscopy [EM-3000 tomey specular microscope]". "Results: The ECD of population 2718.34 ± 320.38 cell/mm2 [range, 1551 to 3376)]. The Avg. /µm2 370.03± 46.99 [range, 232 to 566]. The C.V. 39.3 ±7.66 [range, 25 to 73] and the hexagonal cell per cent 0.507 ± 0.112 [range 0.00 to 0.91]. There were no statistically significant differences in ECD, Avg., C.V. and hexagonal cell per cent between right and left eyes [P= 0.846, P=0.951, P= 0.290, P= 0.419 respectively]. Also there were no statistically significant differences in ECD, Avg., C.V. and hexagonal cell per cent between genders [P= 0.483, P= 0.237, P= o.258 and P= 0.439 respectively]. There were a statistical significant decrease in ECD and hexagonal cell per cent with increase in the age [r= -0.84 and r= -0.72 respectively]. The rate of cell loss was 0.8% per year". Aim of the study:To evaluate the corneal endothelial layer changes in normal Iraqi population with age by using EM-3000 tomey specular microscope.